2012
DOI: 10.1002/lary.23240
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an operating room immersive microlaryngoscopy simulator

Abstract: This study is the first reported study of a high-fidelity microlaryngoscopy simulator with task-specific rating tools. Use of these tools is recommended within otolaryngology training programs, with the global rating assessment for use as a frequently used feedback tool, and the checklist assessment as a confirmatory evaluation of competency at transitions of professional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…125 In the reviewed literature and in other publications, most definitions have embedded within them a minimum standard needed to be safe and/or the ability to perform the operation independently without help. 31,35,45,48,51,53,55,56,[58][59][60][61][62]64,87,103,[105][106][107]109,110,[113][114][115] Surgical competence has been described as a collection of skill, knowledge, and judgment required to complete new or familiar tasks incorporating both technical and nontechnical (ie, clinical problem solving) components. [119][120][121] Furthermore, operative competence builds on this definition but also includes a surgeon's experience and opportunities to form a broader, more universal domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…125 In the reviewed literature and in other publications, most definitions have embedded within them a minimum standard needed to be safe and/or the ability to perform the operation independently without help. 31,35,45,48,51,53,55,56,[58][59][60][61][62]64,87,103,[105][106][107]109,110,[113][114][115] Surgical competence has been described as a collection of skill, knowledge, and judgment required to complete new or familiar tasks incorporating both technical and nontechnical (ie, clinical problem solving) components. [119][120][121] Furthermore, operative competence builds on this definition but also includes a surgeon's experience and opportunities to form a broader, more universal domain.…”
Section: Discussionmentioning
confidence: 99%
“…31,35,45,48,51,53,55,56,[58][59][60][61][62]64,87,103,[105][106][107]109,110,[113][114][115] Differentiating competence from proficiency in the reviewed literature demonstrated that a proficient performer is one who approaches expertise and is thus at an advanced stage compared with a competent performer. 56,62,66,67,69,73,75,76,78-80,82-84,87-89,92-94, 96,97,100,113,116 …”
Section: Definition Of Technical Competencementioning
confidence: 93%
See 2 more Smart Citations
“…To ensure this study was both valid and feasible, we selected a total group study number of 30 in line with recent publications on assessment of surgical skills . However, we acknowledge that to detect a large effect size of Cohen (0.4) with a power of 80%, a total sample size of 66 (22 participants per group) would be required.…”
Section: Discussionmentioning
confidence: 99%